Household organic waste composting using bins with different types of passive aeration - Somjai Karnchanawong (2018)
The objective of this study was to study the performances of six 200-L polyethylene bins, each with different design for passive aeration to organic wastes composting. Food scraps and dry leaves (1.6 kg) were added to each bin once a day until the bin was full. Temperatures at the middle portion were measured daily. The compost from each bin was taken once a week for 120 days for analysis of C, N, volatile solids, and a germination index once a week for 120 days. After 120 days, the compost sample from each bin was taken to determine the mass reduction, size distribution, CEC, N, P and K values. The results showed that the temperatures inside the bins were in the ranges of 24 °C-57 °C. The composts in all bins were found to be stable at around 56-91 days. The wastes decayed fastest in bins with lateral and vertical systems of natural ventilation. It took about two months to stabilize the organic wastes, with a 59-62% decrease of mass. The C/N ratio, CEC, N, P, and K values of the final composts were 14.8-16.0, 66-68 cmol/kg, and 1.26-1.50% N, 0.52-0.56% P2O5and 1.66-1.92% K2O, respectively. © 2011 Elsevier B.V. All rights reserved.